Randomized crossover clinical studies to assess abuse liability and nicotine pharmacokinetics of Velo Oral Nicotine pouches - Kanobe, Milly N.; Powell, Christie Y.; Patrudu, Makena; Baxter, Sarah A.; Tapia, Melissa A.; Darnell, John; Prevette, Kristen; Gibson, Alison G.; Ayoku, Sarah A.; Campbell, Leanne; Coffield, Jeffrey W.; Keyser, Brian M.; et al. (Frontiers in Pharmacology, 2025)
IntroductionOral nicotine pouches (ONPs) are a newer category of smokeless tobacco products containing pharmaceutical-grade nicotine but no tobacco leaf. These products have the potential to help smokers transition away from cigarettes. To assess their potential role as alternatives to cigarettes, we evaluated the abuse liability (AL) of Velo ONPs with varying nicotine content (4–12 mg per pouch), pouch size (600 mg or 400 mg) and flavor (six varieties) in comparison to high (cigarettes) and low (nicotine replacement therapy [NRT] gum) AL comparators.MethodsIndependent randomized crossover clinical studies were conducted to assess AL, including subjective effects (product liking [PL], urge to smoke, product effects, overall PL, and overall intent to use again) and nicotine pharmacokinetic (PK) parameters of Velo ONPs. Participants used test products under controlled conditions, and subjective effect measures were collected using validated questionnaires. Nicotine PK parameters, including peak nicotine concentration (Cmax), time to maximum concentration (Tmax), were assessed.ResultsMean PL scores for all Velo ONPs (p < 0.0042) and Velo Mini Pouches (p < 0.0031) were significantly lower than cigarettes, regardless of nicotine level, pouch size, or flavor, but similar to NRT gum. Other subjective measures for Velo ONPs were less favorable than cigarettes and comparable to or lower than NRT gum. Nicotine uptake with Velo ONPs was slower (reflected by a longer Tmax) and had lower Cmax than cigarettes but was comparable or slightly lower than NRT gum. Overall nicotine uptake increased with increasing nicotine content and was comparable to that of cigarettes for Velo ONPs with higher nicotine levels. Flavor had no effect on nicotine uptake of Velo ONPs.DiscussionVelo ONPs demonstrated an AL profile lower than cigarettes and similar to NRT gum, suggesting a reduced potential for abuse compared to cigarettes. The slower nicotine uptake and lower peak nicotine levels further support their potential as a lower-risk alternative. These findings highlight the potential role of ONPs in tobacco harm reduction strategies by providing an alternative nicotine source with a lower AL than combustible cigarettes.Systematic Review RegistrationThe clinical studies were registered at ClinicalTrials.gov; NCT05129657, NCT05294497, and NCT05081154.